Social effect of Covid-19: Estimates and alternatives for Latin America and the Caribbean - Ivonne Acevedo; Francesca Castellani; Iván Flores; Giulia Lotti; Miguel Székely (Latin American Economic Review, 2020)
This document offers estimates of the possible changes in the social structure of the countries of Latin America derived from the consequent economic contraction from the Covid-19 pandemic and explores the possible costs and benefits of different types of interventions to cushion its impact. The analysis forecasts that the number of people living in poverty (extreme and moderate) would increase by up to 44 thousand million people in the region. It also finds that the policy with the highest benefit-cost ratio is the postponement of payroll taxes and social security contributions. Other alternatives such as granting support to unemployed persons, temporarily doubling the benefits of existing social programs, and the transfer of income to self-employed workers also generate a favorable benefit-cost ratio, with differences among countries.
Keywords: I31; I32; I38; 330; Poverty; inequality; transfers